Care roles and employment decision-making: The effect of economic circumstance. (November 2015) - Austen, Siobhan; Jefferson, Therese; Lewin, Gill; Ong, Rachel; Sharp, Rhonda
This article uses data from a panel of Australian mature-age women to examine the effects of care roles on workers' intentions to leave their jobs. We focus on how the employment effects of care roles can be shaped by the economic circumstances of the worker. We find that caring for an ill, frail or disabled family member has significantly lower effects on the turnover intentions of mature-age women with 'poor' (as compared to favourable) economic circumstances. We interpret this pattern as reflecting the financial costs associated with the provisioning of these types of family care needs.